An Application of Judgement Modeling to Examine Inter-Cultural Differences Regarding Perceptions of Business Skill Importance - zhou, fuzhao; Ken C. Snead; Margo J. Kraft; Aida R. Lozada; Richard N. McGrath; Tania Biswas (International Journal of Business and Social Science Research, 2024)
With increased global interaction, cultural awareness among stakeholders is crucial, especially for companies seeking growth in the international environment. This study focuses on comparing the perceptions of business skill importance between student subjects from China/Hong Kong (CHK) and the United States (US). The results show that the six cues representing the business skills/attributes strongly influenced student perceptions of job offer likelihood and the relative importance of these cues were not equal, with Interpersonal Effectiveness (INPER), Internship Experience (INT), and Ethical Awareness (ETH) having a higher impact than Communication (COMM), Cultural Intelligence (CULT), and Critical Thinking (CRIT). The results indicated that INPER, INT, and ETH were associated with similar, substantial effects, while COMM, CULT, and CRIT exhibited smaller and comparable effects. The analysis revealed significant interactions between the country and two cues Interpersonal Effectiveness (INPER) and Ethical Awareness (ETH). Chinese students perceived INPER to be somewhat more important than U.S. students, possibly influenced by cultural dimensions such as the emphasis on interpersonal relationships in Chinese culture. Conversely, U.S. students regarded ETH as more crucial than their Chinese counterparts, aligning with findings that suggest cultural variations, particularly in power distance and collectivism, may influence ethical values. The findings enhance our understanding of the relative importance of business skills in different cultural contexts and provide insights for educational institutions and employers in preparing students for the global business environment. The study contributes to the existing literature by providing direct comparisons of student perceptions across cultures and employing a rigorous judgment modeling methodology.